ANALYSIS ON THE ENTREPRENEURIAL ACTION AND PUBLIC POLICY AT THE FURNITURE CLUSTER OF UBÁ, MG - Albino, Andréia Aparecida; Lima, Afonso Augusto Teixeira de Freitas de Carvalho; Souza, Sebastião Décio Coimbra de; Behr, Ricardo Roberto; Oliveira, Ronise Suzuki de (Revista de Administração da UFSM, 2010)
Based on recognized importance of industrial clusters for the socio-economic development of regions, this work presents a case study involving the evolution, discussions on the role of entrepreneurial activities and the influence of public policies on the development of the furniture cluster of Ubá, Minas Gerais. The methodology adopted included a survey, interviews with strategic actors of the cluster, and analysis comparative data. Preliminary results indicate that public policies had limited involvement in the emergence and development of APL, and indicate the need to investigate the diversity of patterns of business components of local cluster order to propose appropriate policies for each different type of companies. The main conclusion is that the key role in the genesis and development of the furniture cluster of Ubá was the entrepreneurial action of the local businessmen.